Age‐related telomere attrition causes aberrant gene expression in sub‐telomeric regions. Issue 6 (21st May 2021) - Dong, Xiao; Sun, Shixiang; Zhang, Lei; Kim, Seungsoo; Tu, Zhidong; Montagna, Cristina; Maslov, Alexander Y.; Suh, Yousin; Wang, Tao; Campisi, Judith; Vijg, Jan
Abstract: Telomere attrition has been proposed as a biomarker and causal factor in aging. In addition to causing cellular senescence and apoptosis, telomere shortening has been found to affect gene expression in subtelomeric regions. Here, we analyzed the distribution of age‐related differentially expressed genes from the GTEx RNA sequencing database of 54 tissue types from 979 human subjects and found significantly more upregulated than downregulated genes in subtelomeric regions as compared to the genome‐wide average. Our data demonstrate spatial relationships between telomeres and gene expression in aging. Abstract : Telomere shortening has been found affecting expression of individual genes in subtelomeric regions through a loss of chromosome looping. Using the GTEx RNA database and published Hi‐C data, we demonstrate that this effect indeed occurs during human aging in many tissues, including those for which age‐related telomere attrition has been demonstrated.